Millicomposting: Composting based on the use of diplopods aiming at the production of organic substrates - de Sousa Antunes, Luiz Fernando; Correia, Maria Elizabeth Fernandes; De Andrade Da Silva, Maura Santos Reis [UNESP]; da Silva, Dione Galvão (Centro Universitario de Maringa, 2020)
Millicomposting, a not so well-known biotechnology, involves the biotransformation of vegetable residues into stable organic matter, promoted by the activity of diplopods, popularly known as millipedes. Considering the importance of the substrate in the production of vegetable seedlings, the aim of the present work was to assess the millicomposting technique and evaluate the efficiency of millicompost in the production of seedlings of the American lettuce cultivar Angelina. The millicompost consisted of Bauhinia sp. (cow’s foot leaves), Paspalum notatum (grass clippings), Musa sp. (banana leaves), and cardboard. Physical, physicochemical, and chemical analyses of the obtained millicompost were performed 180 days into the experiment. The lettuce seedlings were grown in expanded polystyrene trays of 200 cells and the evaluations occurred 30 days after sowing. The evaluated phytotechnical characteristics were fresh and dry shoot mass, fresh and dry root mass, plant height, number of leaves, seedling vigor, and clod stability. The millicompost had a higher total nutrient content and lower volume density than the Biomix® organic substrate. All of the developmental parameters of the lettuce seedlings differed between the millicompost and the Biomix® organic substrate; all of the mean values were higher for the millicompost, except for the number of leaves, which did not differ from the Biomix® organic substrate. The millicomposting process facilitated the reuse of organic waste by converting it into quality organic compost and resulted in the efficient production of excellent quality lettuce seedlings.
Gongocompostagem: A compostagem baseada na utilizaÇÃo de diplÓpodes visando a produÇÃo de substratos org nicos
Keywords: Horticulture; Millipedes; Organic compounds; Quality seedlings